2008
DOI: 10.1108/02621710810849362
|View full text |Cite
|
Sign up to set email alerts
|

Assessing managerial skills in SMEs for capacity building

Abstract: PurposeThe paper aims to identify perceived critical managerial factors (PCMFs) affecting the performance of SMEs, show the direction and extent of relationship between PCMFs and firm characteristics, and forward some research and policy implications.Design/methodology/approachThe paper uses a survey questionnaire to collect data on SMEs' perceptions of the degree of impact of selected managerial issues on their performance. The data were factor analyzed (principal component analysis), purified (Varimax rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 8 publications
1
42
0
1
Order By: Relevance
“…In terms of policy implications, our finding of a negative relationship between board size and the performance of both small and medium firms leads us to recommend that, given the limited resources of SMEs (Pansiri and Temtime, 2008), they need to focus their attention on reducing board size to an optimal level. A positive relationship between CEO age and the performance of medium firms suggests that such firms should encourage their CEOs to remain in post for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of policy implications, our finding of a negative relationship between board size and the performance of both small and medium firms leads us to recommend that, given the limited resources of SMEs (Pansiri and Temtime, 2008), they need to focus their attention on reducing board size to an optimal level. A positive relationship between CEO age and the performance of medium firms suggests that such firms should encourage their CEOs to remain in post for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…Afraz et al (2014) also identified constraints and barriers to growth of small firms in Pakistan. Thus, there is a need for raising the awareness of Pakistani SMEs of the important role performance appraisal could play in improving the performance of SMEs (Ichniowski et al, 1997;Lange et al, 2000;Pansiri & Temtime, 2008) especially in view of the mentioned growth phase in which Pakistani SMEs find themselves. The adoption of formal practices such as a 360 degree appraisal method, management by ojectives, assessment centres, provision of training to managers who appraise performance, and provision of training to employees who recieve performance appraisal could enhance the performance profile of SMEs (Bartel, 2004).…”
Section: Journal Of Management Sciencesmentioning
confidence: 99%
“…Previous research has found that management decision-making and organizational structure revolves around the preferences and interests of owner-managers who take all the major decisions and monitor all activities. (Pansiri et al, 2006;Hitt et al 1996). While such approaches and structures enable strong control over the firm, organizational success or failure in SMEs is seriously affected by the managerial competencies of the owner-managers.…”
Section: Business Skillsmentioning
confidence: 99%